Women in the press pages of Rondonópolis /MT: a study of representations and social roles in the 1980s - Ana Gonçalves Souza; Adriana Aparecida Pinto (Revista Eletrônica História em Reflexão, 2017)
This article aims to present how women were represented in the newspaper A Tribuna, analyzing the local press discourse on the role and social place attributed to women in the 1980s, seeking to understand the forms of resistance and maintenance of order and of a male-dominated society, who still conceived the place of the woman in the private sphere of and the men in the public sphere. The newspaper A Tribuna began its circulation in the city of Rondonópolis on June 7, 1970 and circulates to the present day in printed format and since 2005 in print and digital format. This device transmits in its pages some stories that present the city of Rondonopolis with a strong emphasis on its economy since 1970, during which time it received a strong migratory flow from various regions of the country, highlighting the northeast and south regions.